Integrated Parking System For Troubleshooting Parking Location Search In Big City Based Internet Of Things (IoT) - tri raharjo yudantoro (Politeknik Negeri Semarang, 2017)
Parking space is one of the important needs for vehicle owners.along with the increasing number of vehicles, especially in big cities have an impact on the difficulty of finding parking locations. Sometimes it takes a few minutes even hours just to find the location of available parking. This is the background of making Finding Parking. Application Finding Parking is an online parking search system based on the Internet of Things.on the parking location there are infrared sensors that aims to detect the presence of vehicles, data from existing sensors this parking location will be processed and sent to users who look for parking locations via Android to know the location of the nearest parking. The purpose of this Final Project is to help vehicle owners find available parking locations.Finding Parking application created by Waterfall method, Java programming language, MySQL database that is run by users through Android smartphone .Based on the tests that have been done can be obtained results that Finding Parking application is able to provide information to the owner of the vehicle regarding the availability of parking locations.